Endothelial nitric oxide synthase-derived nitric oxide in the regulation of metabolism - Tenopoulou, Margarita (F1000Res, 2020)
Nitric oxide is an endogenously formed gas that acts as a signaling molecule in the human body. The signaling functions of nitric oxide are accomplished through two primer mechanisms: cGMP-mediated phosphorylation and the formation of S-nitrosocysteine on proteins. This review presents and discusses previous and more recent findings documenting that nitric oxide signaling regulates metabolic activity. These discussions primarily focus on endothelial nitric oxide synthase (eNOS) as the source of nitric oxide.